2008
DOI: 10.1149/1.2828010
|View full text |Cite
|
Sign up to set email alerts
|

In Situ Electrochemical STM Study of Potential-Induced Coarsening and Corrosion of Platinum Nanocrystals

Abstract: In situ electrochemical scanning tunneling microscopy was used to study the coarsening of platinum nanocrystals under potentiostating and the dissolution and coarsening of platinum nanocrystals through potential cycling. A rapid coarsening of platinum nanocrystals was observed for potentiostating in the double-layer region. No obvious crystal size changes were observed for potentiostating in the platinum oxidation-reduction region and the hydrogen-adsorption proton-oxidation region. The coarsening is proposed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
31
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(32 citation statements)
references
References 26 publications
1
31
0
Order By: Relevance
“…The only difference is in the initial grain size, which were smaller for Pt-Co (7 nm) than for pure Pt (8 nm). An increase of the particles size of pure Pt under potential cycling is in agreement with previously reported results [21,23].…”
Section: Resultssupporting
confidence: 93%
“…The only difference is in the initial grain size, which were smaller for Pt-Co (7 nm) than for pure Pt (8 nm). An increase of the particles size of pure Pt under potential cycling is in agreement with previously reported results [21,23].…”
Section: Resultssupporting
confidence: 93%
“…30,34) Let us assume that a pit is formed, as shown in Fig. 7, as a result of Co-selective dissolution and Pt-surface diffusion; 17,18) i.e., the pit wall consists of pure Pt and Co atoms are exposed at the pit bottom. Accordingly, the coverage of pits (ª) can be given by the fraction of Co atoms in PtCo alloys, irrespective of the size and the number of pits.…”
Section: Selective Dissolution and Surface Morphologymentioning
confidence: 99%
“…Xu et al applied EC-STM to track the coarsening occurring on a polycrystalline Pt electrode during potential holds at different potentials. [28] They found that the surface reconstruction, attributed to adatom diffusion processes, is most pronounced when the potential is held in the so-called double layer region, as at lower and higher potentials the surface of Pt is covered by protons and oxygenated species, respectively. The most stable surface orientation of the formed grains was Pt (111), in accord with ex situ observations.…”
Section: Investigations With Model Bulk Electrodes: Understanding Pt mentioning
confidence: 99%